Penerapan Metode Pembelajaran Berbasis Proyek Sebagai Solusi Permasalahan Siswa Kurang Menyukai Pembelajaran Matematika - Inri Ani Gultom; Naswa Amirah; Della Nanda Sidabalok; Sri Rahayu; Sushmita Marina Angel (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research uses qualitative method, case study, to find out how effective the use of project-based learning (PjBL) method is to increase elementary students' interest and desire to learn mathematics. Interviews with teachers and students, participant observation, and document analysis are all methods used to collect research data. The results showed that the PjBL method proved effective in increasing elementary students' interest and desire to learn mathematics. This is shown by an increase in students' active participation in lessons, an increase in students' curiosity about math topics, and an increase in their math learning outcomes.